2020
DOI: 10.1111/beer.12292
|View full text |Cite
|
Sign up to set email alerts
|

“Me” versus “We” in moral dilemmas: Group composition and social influence effects on group utilitarianism

Abstract: The paper is one of the first empirical attempts that builds on the moral dilemmas and group rationality literature to explore the way in which group composition with respect to group members’ individual choices in moral dilemmas and social influence processes impact on group moral choices. First individually and then, in small groups, 221 participants were asked to decide on 10 moral dilemmas. Our results show that emergent group level utilitarianism is higher than the average individual utilitarianism, yet, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…Consequently, our findings are inconsistent with the Social Deliberation (SD) and Virtue-Signaling (VS) hypotheses and in favor of the Stress Reduction (SR) hypothesis (see Figure 1). A recent study that used a rather similar design (Curşeu et al, 2020) also showed a utilitarian boost at the collective (vs. the first individual) level. However, since they did not measure post-discussion private decisions, their findings did not distinguish between our Social Deliberation and Stress Reduction hypotheses.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Consequently, our findings are inconsistent with the Social Deliberation (SD) and Virtue-Signaling (VS) hypotheses and in favor of the Stress Reduction (SR) hypothesis (see Figure 1). A recent study that used a rather similar design (Curşeu et al, 2020) also showed a utilitarian boost at the collective (vs. the first individual) level. However, since they did not measure post-discussion private decisions, their findings did not distinguish between our Social Deliberation and Stress Reduction hypotheses.…”
Section: Discussionmentioning
confidence: 83%
“…This hypothesis, therefore, predicts that the second individual judgments would also be more utilitarian than the first individual judgments, specifically for the scenarios discussed collectively. Indeed, a recent work that investigated moral reasoning in groups of students (Curşeu et al, 2020) found that discussion in groups led to more utilitarian decisions. However, this study did not measure individual opinions after the discussion, leaving open any conclusions about the mechanisms at play.…”
Section: Current Study: Moral Judgment In the Social Arenamentioning
confidence: 99%
“…Moreover, groups in which members differ in terms of their level of expertise, education, rationality, or cognitive competencies exhibit horizontal differentiation to some extent, while the unequal distribution of these cognitive resources within groups leads to vertical status differences and unequal allocation of idiosyncrasy credit within groups (Hollander, 1958). All studies in which cognitive diversity was assessed as the within-group standard deviation of individual rationality or cognitive competencies reveal negative associations of cognitive diversity with synergetic group performance in decision tasks (Curşeu et al, 2013(Curşeu et al, , 2015(Curşeu et al, , 2020 and performance (Kilduff et al, 2000). One exception is the study of Martins et al (2013) that reported a positive association between expertness diversity (evaluated as within-group standard deviation of CGPA) and group performance in an IT project realized as part of a course task.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that there is a negative correlation between group fragmentation concerning group members' individual rationalities (as an index of cognitive diversity) and strong cognitive synergy (Curşeu & Schruijer, 2012;Curşeu et al, 2013Curşeu et al, , 2015. Moreover, Curşeu et al (2020) found that emergent group-level utilitarianism is positively predicted by the average individual utilitarianism of the group members and negatively impacted by group-level fragmentation in utilitarianism. Group utilitarianism is lower than the highest individual utilitarianism but exceeds the average individual utilitarianism.…”
Section: Topicsmentioning
confidence: 98%
“…Normative conformity is high when opinions held by the majority are accepted by all group members (Curs eu et al, 2020). People conform to social norms for obtaining social approval, making accurate choices and maintaining positive self-concept (Cialdini and Goldstein, 2004).…”
Section: Team Knowledge-sharing Motivationsmentioning
confidence: 99%